PENGARUH GAYA KEPEMIMPINAN, KEPUASAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA POLITEKNIK PELAYARAN BAROMBONG: The Influence of Leadership Style, Job Satisfaction, and Organizational Culture on Employee Performance at the Barombong Shipping Polytechnic - Hamka Mappiasse; Maryadi Maryadi; Sylvia Sjarlis (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat ITB Nobel Indonesia, 2022)
Abstract Abstract Hamka Mappiasse. 2022. The Influence of Leadership Style, Job Satisfaction, and Organizational Culture on Employee Performance at the Barombong Shipping Polytechnic, supervised by Maryadi and Sylvia Sjarlis. This study aims to determine and analyze leadership style, job satisfaction and organizational culture partially and simultaneously on employee performance at the Barombong Shipping Polytechnic. Research design is defined as a strategy to carry out research. If classified by type, then this research is classified as a level of explanation or explanation level research. The population used in this study were all employees at the Barombong Shipping Polytechnic, amount to 200 employees. The determination of the sample in this study uses Arikunto's opinion in Saban, Echdar (2017) that if the number of subjects is large (greater than 100), it can be taken between 10-15% or 20-55%, or more depending on the number of: the ability of the researcher in terms of time, energy and funds. Based on this opinion, the sample of this study was determined at 25% x 200 population = 50 employees. The results of this study indicate that the results of the F test or simultaneous testing show that calculated value is 15.541 and the F-table 2.80. So it shows that F-count > F-table with a significance of 0.000 < 0.05. These results indicate that simultaneously leadership style, job satisfaction and organizational culture on employee performance at the Barombong Shipping Polytechnic. From the description of the T-test, it is known that the T-value of the variable leadership style, job satisfaction and organizational culture partially has a positive and significant effect on the performance of Barombong Shipping Polytechnic employees. Furthermore, the leadership style variable is the most dominant influencing variable with a beta value of 0.440. Keywords: Leadership Style, Job Satisfaction, Organizational Culture and Performance